1969
DOI: 10.1007/bf00189940
|View full text |Cite
|
Sign up to set email alerts
|

On the pop-in mode of fracture

Abstract: Expertmental observataons concerning the pop-m mode of fracture obtained during an investigation of the fracture toughness of glassy plastics are related. Comments on the mechanics of the pop-in mode are presented,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

1975
1975
1994
1994

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 3 publications
0
8
0
2
Order By: Relevance
“…Key [18] found that the greatest value of GI occurs for an internal fiat elliptical crack propagating along its minor semi-axis b. This indicates that GI corresponding to Case 2 is energetically the most favourable growth mode of all the possible cracking possibilities.…”
Section: Internal Flat Elliptical Crackmentioning
confidence: 94%
See 4 more Smart Citations
“…Key [18] found that the greatest value of GI occurs for an internal fiat elliptical crack propagating along its minor semi-axis b. This indicates that GI corresponding to Case 2 is energetically the most favourable growth mode of all the possible cracking possibilities.…”
Section: Internal Flat Elliptical Crackmentioning
confidence: 94%
“…For a 3-D flaw, 'global' energy release rates Gl may vary with possible virtual crack extensions (e.g. [18,19]). On the other hand, for a fiat crack with a curved front, 'local' stress intensity factors 1([ may vary along the crack front (e.g.…”
Section: Gl -Os Lxs-+o As'mentioning
confidence: 99%
See 3 more Smart Citations